Available Nitrogen Nutrient Levels (NO3-) with Organic Fertilizer Treatment and Its Correlation to the Growth and Yield of Peanut Plants (Arachis hypogaea L.): Kadar Hara Nitrogen Tersedia (NO3-) dengan Perlakuan Pupuk Organik dan Koerlasinya terhadap Pertumbuhan dan Hasil Tanaman Kacang Tanah (Arachis hypogaea L.) - Rahmat Abdullah; Nurmi Nurmi; Fitriah S.Jamin (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2024)
Peanut plants require Nitrogen nutrient content to increase plant growth and maximum production. Increasing nitrogen nutrients in the soil can be obtained through the addition of organic fertilizers. The purpose of this study was to determine the effect of organic fertilizers (burnt rice husks and chicken manure) on NO3- nutrient levels in peanut plants, to determine organic fertilizers (burnt rice husks and chicken manure) that will provide the highest NO3- nutrient levels in peanut plants (Arachis hypogaea L.) and to determine the correlation between NO3- nutrient levels with the growth and yield of peanut plants (Arachis hypogaea L.). This study was conducted from September to November 2022 in Toto Utara Village, Tilongkabila District, Bone Bolango Regency. The study used a Randomized Kelompaok Design (RAK) consisting of 3 treatment levels, namely P0 = without organic fertilizer, P1 = chicken manure 3kg/plot, and P2 = burnt rice husk fertilizer 3kg/plot. Each treatment was repeated 4 times so that there were 12 units/plot. The results of this study indicate that organic fertilizers have a significant effect on NO3- nutrient levels with NO3- nutrient levels in the chicken manure treatment of 0.89 (ppm) and in the burnt rice husk fertilizer treatment of 0.61. There is a strong and very strong positive linear correlation between plant height, number of pods, seed weight per plant, and seed weight per hectare with NO3- nutrient levels.